2009
DOI: 10.1007/s12522-009-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of lipids in day 7–13 blastocysts, serum and uterine fluid of rabbits

Abstract: Palmitic acid is the most abundant fatty acid in the blastocysts, serum and uterine fluids of rabbit during days 7-13 of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…PUFA in general, and linolenic acid in particular, support essential development processes in mammalian embryos [ 26 ]. Linoleic acid acts as a precursor for eicosanoids and regulates the processes of endocytosis or exocytosis, ion channel modulation, DNA polymerase inhibition and gene expression [ 27 ]. Moreover, linoleic acid stimulates protein kinase C, which is necessary for cell differentiation and growth [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PUFA in general, and linolenic acid in particular, support essential development processes in mammalian embryos [ 26 ]. Linoleic acid acts as a precursor for eicosanoids and regulates the processes of endocytosis or exocytosis, ion channel modulation, DNA polymerase inhibition and gene expression [ 27 ]. Moreover, linoleic acid stimulates protein kinase C, which is necessary for cell differentiation and growth [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early morulae and compacted morulae can be found at 72 hpm. Palmitic acid, as the main SFA, was identified in abundant concentrations in more developed embryos [ 27 ] and is reported to be essential for FA elongation and desaturation in embryo development [ 34 ]. Moreover, incubation with palmitic acid showed that embryos can oxidize palmitic acid even at the single-cell stage, with subsequent increases, particularly from four-cell embryos onwards [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In embryos, similar protection mechanisms might exist; Tsujii et al. () found higher concentrations of saturated fatty acids than unsaturated fatty acids in rabbit embryos.…”
Section: The Influence Of Fat Feeding On the Oocytes And Embryonic LImentioning
confidence: 94%
“…Also, Tsujii et al. () emphasized that serum and oviduct fluids play an important role in the development of blastocysts. The concentrations of nutrients in tubal fluid are documented to be below their plasma concentrations (Leese and Barton ), which suggests that their overall transport across the tube occurs principally by diffusion (Leese and Gray ).…”
Section: Fat Feeding and The Effects On The Oocyte And Embryo Microenmentioning
confidence: 99%
“…We then demonstrated that the lipid-rich inter-muscular environment allows fabT mutant growth in a FASII-dependent manner, while inhibiting the WT strain. While the overall muscle and uterine fluids environments where GAS multiply are very different, it is notable that their lipid concentrations, differ by ~1000-fold (150 mg/g muscle, compared to 20-200 µg/ml in uterine fluid 29,30 ). We suggest that exposure to high inter-muscular lipid availability would contribute to WT mortality.…”
Section: Discussionmentioning
confidence: 99%